Pengembangan Sistem Nanostructured Lipid Carriers (NLC) Meloxicam dengan Lipid Monostearin dan Miglyol 808 Menggunakan Metode Emulsifikasi - Rahmi Annisa; Esti Hendradi; Dewi Melani (Mulawarman University, 2016)
The aim this study was to determine the effect of Monostearin and Miglyol 808 lipid ratio in NLC system formulation resulting in physicochemical characteristics, release rate, and penetration rate. The NLC making was done by using emulsification method. In the formulation of NLC meloxicam, 3 different lipid ratios were used, including ratios of 6:4, 7:3, 8:2.  Meloxicam served as active ingredient, monostearin served as solid lipid, miglyol 808 served as a liquid lipid, and tween 80 was surfactant. NLC meloxicam physicochemical characteristics include tests of organoleptic, pH, viscosity, particle size, particle morphology and entrapment efficiency. NLC meloxicam belongs to semisolid preparations with pH value range of 5,72-5,87. Increasing viscosity of NLC system are cause by increase of solid lipid. The measurement results of particle size of three different lipid formulas indicated that the lipid particle size was <1000 nm. Test of NLC particle morphology by using Transmission Electron Microscopy (TEM) indicated the spherical particle shape (round). Entrapment efficiency test of all NLC-lipid compositions revealed quite high result (> 80%). The determination of release rate (flux) and penetration rate (flux) was conducted by using Franz diffusion cells with a cellophane membrane for the release and Wistar ratâ€™s skin membrane for the penetration. The release rate values of three NLC meloxicam formulas showed p value (sig) 0,005, while the penetration rate obtained p value (sig) 0,091. Keywords: NLC, meloxicam, physicochemical characterization, release rate and penetration rate